Water on Mars, With a Grain of Salt: Local Heat Anomalies Are Required for Basal Melting of Ice at the South Pole Today - Michael M. Sori; Ali M. Bramson (Geophysical Research Letters)
Abstract Recent analysis of radar data from the Mars Express spacecraft has interpreted bright subsurface radar reflections as indicators of local liquid water at the base of the south polar layered deposits (SPLD). However, the physical and geological conditions required to produce melting at this location were not quantified. Here we use thermophysical models to constrain parameters necessary to generate liquid water beneath the SPLD. We show that no concentration of salt is sufficient to melt ice at the base of the SPLD in the present day under typical Martian conditions. Instead, a local enhancement in the geothermal heat flux of >72 mW/m2 is required, even under the most favorable compositional considerations. This heat flow is most simply achieved via the presence of a subsurface magma chamber emplaced 100 s of kyr ago. Thus, if the liquid water interpretation of the observations is correct, magmatism on Mars may have been active extremely recently.